PERLINDUNGAN HUKUM HAK CIPTA ATAS OBJEK MUSIK DAN/ATAU LAGU - Nathaniela Putri Arumdhani; Iwan Erar Joesoef (Fakultas Hukum, Universitas Halu Oleo, 2021)
The purpose of this study is to examine the legal protection of copyright holders for music and songs. Creative Economy (Ekraf) more or less affects the economic growth of a country through optimizing the concept of Intellectual Property Rights (IPR). Music and/or songs are one of the products produced by the creative industry that is protected by law, one of which is by granting copyright and providing financial benefits in the form of royalties for music and/or songs to the creator. The findings of this study, these rights are still often ignored. One of the reasons is because there is no clarity regarding the collection of music and/or song royalties and how the management system will be until later it can be accepted by the Copyright holder, in this case the music and/or song creator. This research is a normative legal research using secondary data in the form of primary and secondary legal materials, as well as a statutory approach which is then compiled qualitatively. The conclusion of this study shows that the copyright protection system for creators of works is provided by the government through Government Regulation Number 56 of 2021 concerning Management of Song and/or Music Copyright Royalties, protection and legal certainty for creators, copyright holders, and rights owners related to economic rights to music and/or songs. For this reason, transparency is needed regarding the management of copyright royalties by the National Collective Management Institute (LMKN) as well as audits.